The effect of bitter gourd (Momordica charantia) ethanolic extract on inflammatory infiltrates and NF-κB activation in periodontitis - Aryudhi Armis; Tetiana Haniastuti; Heni Susilowati (Majalah Kedokteran Gigi Indonesia, 2019)
Periodontitis is a periodontal disease involving the gingiva, periodontal ligament, cementum, and alveolar bone due to an inflammatory process. Virulence factors of periodontopathogens and inflammatory responses in periodontitis can stimulate nuclear factor-kappa B (NF-κB) activity. Charantoside c and Momordicosides g in bitter gourd prevent NF-κB activation stimulated by TNF-α in HepG2 cells. This study aims to determine the effect of bitter gourd fruit (Momordica charantia) ethanolic extract as an anti-inflammatory substance on the level of inflammatory infiltrates and the number of cells that experience NF-κB activation in the periodontitis model. Eighty male Wistar rats were divided into 5 groups. The mandibular incisors were ligated for 14 days to induce periodontitis. Each group was given Momordica charantia extract of 500 mg/kg BW, 250 mg/kg BW, and 100 mg/kg BW; ibuprofen 100 mg/kg BW; and aquades orally using oral gavage on the day 14. Rat necropsy was carried out on day 1, 3, 5, and 7 after giving the substances. Taking out the lower jaw was done to make tissue preparations followed by staining them with hematoxylin eosin (HE). Immunohistochemicalanalysis was performed to observe cells that were positive for NF-κB activation. The results showed a decrease in the density of inflammatory infiltrates in all groups, except for those given aquades. The number of inflammatory cells ofneutrophils, macrophages, and lymphocytes that experienced NF-κB activation showed the most effective decrease in the group of Momordica charantia 500 mg/kg BW, on the 7th day. The conclusion of this study is that ethanolic extractof Momordica charantia has an anti-inflammatory effect and prevents the activation of NF-kB in rat gingival induced by periodontitis. The highest effect was found at a dose of 500 mg/kg BW on day 7 after giving of extracts.